Pediatric cartilaginous lateral femoral condyle Hoffa fracture: a case report and review of the literature - A. de Beer; M. J. Brown (BMC, 2023)
Abstract Introduction Hoffa fractures are challenging coronally-oriented articular injuries of the femoral condyle. These fractures are rare in adults and extremely rare in the skeletally immature, with few cases reported in literature. To prevent mal- or non-union, Hoffa fractures require prompt surgical stabilisation with anatomic reduction and internal fixation. Case report We discuss the case of a lateral distal femoral condyle cartilaginous Hoffa fracture in a ten-year-old male patient. The patient presented after a football non-contact "twist and pop" injury with radiographic imaging described as an osteochondritis dissecans lesion. An MRI was obtained which demonstrated a lateral distal femoral condyle osteochondral fracture. An operative plan was formulated to perform arthroscopic reduction and bio-compression screw fixation to minimize damage to the physis and surrounding tissues. Hyperflexion of the knee allowed for anatomic fracture reduction with the placement of 2 bio-compression screws serving as maintenance of fixation. The patient did well postoperatively and returned to full activity after 6 months. Conclusion Hoffa fractures in the pediatric population are rare and can occur not only through bone but also through the thick chondral layer in younger patients. These are extremely difficult to diagnose through X-Ray alone. The prompt use of MRI imaging allows for operative fixation in a timely fashion, while an arthroscopic-only approach allows for minimal tissue damage. With an appropriate fracture type, hyper-flexion reduces and stabilizes the fracture, permitting the placement of minimally invasive bio-compression fixation.